2011
DOI: 10.1002/jbm.a.33306
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor release from a chemically modified elastomeric poly(1,8‐octanediol‐co‐citrate) thin film promotes angiogenesisin vivo

Abstract: The ultimate success of in vivo organ formation utilizing ex vivo expanded "starter" tissues relies heavily upon the level of vascularization provided by either endogenous or artificial induction of angiogenic or vasculogenic events. To facilitate proangiogenic outcomes and promote tissue growth, an elastomeric scaffold previously shown to be instrumental in the urinary bladder regenerative process was modified to release proangiogenic growth factors. Carboxylic acid groups on poly(1,8-octanediol-co-citrate) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The findings revealed that the level of structural disc degeneration is most strongly related to the amount of disc tissue disruptions due to the puncture rather than the injectate. The concentrations of TNFα and NGF/VEGF were adopted from previous in vivo or in vitro studies [3740], and were sufficient to induce observable changes in pain behavior in this study. The deeper annular puncture induced both NP and AF injury with no herniation observed in all injected discs by MRI or histology, although the full AF depth injury could result in some NP exposure in the anterior region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that the level of structural disc degeneration is most strongly related to the amount of disc tissue disruptions due to the puncture rather than the injectate. The concentrations of TNFα and NGF/VEGF were adopted from previous in vivo or in vitro studies [3740], and were sufficient to induce observable changes in pain behavior in this study. The deeper annular puncture induced both NP and AF injury with no herniation observed in all injected discs by MRI or histology, although the full AF depth injury could result in some NP exposure in the anterior region.…”
Section: Discussionmentioning
confidence: 99%
“…All intradiscal injections used a 26-gauge needle at a depth of 1.5 mm (shallow) or 3 mm (deep) as guided by a needle stopper. A total of 2.5 μL of PBS, TNFα (0.25 ng in 2.5 uL) [37], or NGF/VEGF (50 ng/250 ng in 2.5 uL) were slowly injected into each disc using a calibrated microliter syringe (Hamilton Company, Reno, NV, USA) with doses taken from the literature [3840]. The volume and method of intradiscal injection were determined from thorough preliminary studies on motion segments of live animals that titrated the injection volume down to 2.5 μL and demonstrated that there was no fluid leakage or nerve root irritation were visible.…”
Section: Methodsmentioning
confidence: 99%
“…After 10 weeks of implantation to augment partially cystectomized nude rats, POC-augmented bladders seeded with mesenchymal stem and urothelial cells displayed normal tissue architecture and 1.75 times greater muscle/collagen ratios than did films seeded with smooth muscle and urothelial cells, thus demonstrating their potential to support partial bladder regeneration in vivo. To promote angiogenesis and improve bladder regeneration, the carboxylic acid groups of POC were modified with heparan sulfate to create heparan-binding domains for the subsequent conjugation of proangiogenic growth factors (126). A threefold increase in release of vascular endothelial growth factor, fibroblast growth factor 2, and insulin-like growth factor 1 was observed for heparan-modified POC versus controls during a 30-day time course in vitro.…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 99%
“…Bioengineering of blood vessels has been investigated for nonbladder tissues, while cells (mesenchymal stem cells, endothelial cells) and growth factors have been used to enhance vascular growth into bladder grafts. [22][23][24][25][26][27][28] The results of this study suggest that pre-existing vessels in bioengineered grafts might facilitate early perfusion and enhance graft regeneration and function in the long term. As such, the engineering of graft blood vessels and the promotion of inosculation between host and donor vessels, either endogenous or engineered, might promote graft success, thereby potentiating the use of bioengineered bladder tissue for transplantation.…”
mentioning
confidence: 83%